2x(x-13)^2 - x^2(x-13) = 0Упростим:
2x(x^2 - 26x + 169) - x^3 + 13x^2 = 02x^3 - 52x^2 + 338x - x^3 + 13x^2 = 0x^3 - 39x^2 + 338x = 0x(x^2 - 39x + 338) = 0x(x - 13)(x - 26) = 0
Таким образом, корнями уравнения являются:x1 = 0x2 = 13x3 = 26
Ответ: x1 = 0, x2 = 13, x3 = 26
2x(x-13)^2 - x^2(x-13) = 0
Упростим:
2x(x^2 - 26x + 169) - x^3 + 13x^2 = 0
2x^3 - 52x^2 + 338x - x^3 + 13x^2 = 0
x^3 - 39x^2 + 338x = 0
x(x^2 - 39x + 338) = 0
x(x - 13)(x - 26) = 0
Таким образом, корнями уравнения являются:
x1 = 0
x2 = 13
x3 = 26
Ответ: x1 = 0, x2 = 13, x3 = 26